Nanoscopy for endosomal escape quantification. Issue 1 (19th November 2020) - Andrian, Teodora; Riera, Roger; Pujals, Silvia; Albertazzi, Lorenzo
Abstract : How nanoscopy can be applied towards the study and quantification of endosomal escape of nanoparticles. Abstract : The successful cytosolic delivery of nanoparticles is hampered by their endosomal entrapment and degradation. To push forward the smart development of nanoparticles we must reliably detect and quantify their endosomal escape process. However, the current methods employed are not quantitative enough at the nanoscale to achieve this. Nanoscopy is a rapidly evolving field that has developed a diverse set of powerful techniques in the last two decades, opening the door to explore nanomedicine with an unprecedented resolution and specificity. The understanding of key steps in the drug delivery process – such as endosomal escape – would benefit greatly from the implementation of the most recent advances in microscopy. In this review, we provide the latest insights into endosomal escape of nanoparticles obtained by nanoscopy, and we discuss the features that would allow these techniques to make a great impact in the field.